KEPENTINGAN INDONESIA MELAKUKAN KERJASAMA DENGAN INGGRIS DALAM BIDANG PENGEMBANGAN ENERGI - Akbar, Mummahid Thariq; Yealta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The problem of energy cannot be separated from the geopolitical conception that looks at the geographical position of a country as a component of its capabilities in the international political order. The energy context if analyzed in the perspective of International Political Economy is based on the interdependence relationship between countries within the scope of economic dependence between countries. The form of interdependence between countries is the export-import activities between countries, cooperation between countries in finding new energy sources and securing energy supplies in other countries.The need of energy supplies in Indonesia, especially on diesel demand is increasing every year. However, this increase could not be fulfilled by national oil based energy supply due to the decrease of oil production and there has not been significant increase in term of oil fractionation plants. As a consequence, diesel import could not be avoided resulting an additional burden in nation budgeting.To overcome this problem, LNG might be an alternative. Thus, diesel imports can be eliminated further, domestic industries can be more competitive. Indonesia is one of the leading LNG producers in the world, most of the LNG production is exported to China, Korea and Mexico. Currently the government is paying more attention to the LNG sector because it is expected to be a more effective alternative energy than others. Keywords : Cooperate, Energy, Energy Development, Indonesia, Britain.